Impact of High-Deductible Health Plans on Emergency Department Patients With Nonspecific Chest Pain and Their Subsequent Care. Issue 5 (3rd August 2021) - Chou, Shih-Chuan; Hong, Arthur S.; Weiner, Scott G.; Wharam, J. Frank
Abstract : Background: Timely evaluation of acute chest pain is necessary, although most evaluations will not find significant coronary disease. With employers increasingly adopting high-deductible health plans (HDHP), how HDHPs impact subsequent care after an emergency department (ED) diagnosis of nonspecific chest pain is unclear. Methods: Using a commercial and Medicare Advantage claims database, we identified members 19 to 63 years old whose employers exclusively offered low-deductible (⩽500) plans in 1 year, then, at an index date, mandated enrollment in HDHPs (≥1000) for a subsequent year. We matched them with contemporaneous members whose employers only offered low-deductible plans. Primary outcomes included population rates of index ED visits with a principal diagnosis of nonspecific chest pain, admission during index ED visits, and index ED visits followed by noninvasive cardiac testing within 3 and 30 days, coronary revascularization, and acute myocardial infarction hospitalization within 30 days. We performed a cumulative interrupted time-series analysis, comparing changes in annual outcomes between the HDHP and control groups before and after the index date using aggregate-level segmented regression. Members from higher-poverty neighborhoods were a subgroup of interest. Results: After matching, we included 557 501 members in the HDHP group and 5 861 990 in the control group, with mean ages of 42.0 years, 48% to 49% female, and 67% to 68% non-Hispanic White individuals. Employer-mandated HDHP switches were associated with a relative decrease of 4.3% (95% CI, –5.9 to –2.7; absolute change, –4.5 [95% CI, –6.3 to –2.8] per 10 000 person-years) in nonspecific chest pain ED visits and 11.3% (95% CI, –14.0 to –8.6) decrease (absolute change, –1.7 per 10 000 person-years [95% CI, –2.1 to –1.2]) in visits leading to hospitalization. There was no significant decrease in subsequent noninvasive testing or revascularization procedures. An increase in 30-day acute myocardial infarction admissions was not statistically significant (15.9% [95% CI, –1.0 to 32.7]; absolute change, 0.3 per 10 000 person-years [95% CI, –0.01 to 0.5]) but was significant among members from higher-poverty neighborhoods. Conclusions: Employer-mandated HDHP switches were associated with decreased nonspecific chest pain ED visits and hospitalization from these ED visits, but no significant change in post-ED cardiac testing. However, HDHP enrollment was associated with increased 30-day acute myocardial infarction admission after ED diagnosis of nonspecific chest pain among members from higher-poverty neighborhoods. Abstract : Supplemental Digital Content is available in the text.